The CXCR4 antagonist R54 targets epithelial-mesenchymal transition (EMT) in human ovarian cancer cells. - Daniela Russo; Anna Spina; Luigi Portella; Anna Maria Bello; Francesca Galdiero; Anna Maria Trotta; Caterina Ieranò; Giuseppina Rea; Sabrina Chiara Cecere; Elisabetta Coppola; Salvatore Di Maro; Sandro Pignata; et al. (PLoS ONE)
The axis CXCL12-CXCR4 is highly expressed in ovarian cancer where contributes to disease progression. Aim of the work was to evaluate the effect of the newly developed CXCR4 antagonist R54 on human ovarian cancer cells aggressiveness. CXCL12-CXCR4 axis was evaluated in human ovarian cancer cells through proliferation, migration and signaling CXCL12-dependents. Epithelial to mesenchymal transition (EMT) was analyzed through E-CADHERIN, N-CADHERIN, VIMENTIN, SNAIL1 and ΒETA-CATENIN by qRT-PCR, immunofluorescence and immunoblotting. R54 inhibited ovarian cancer cells proliferation and migration CXCL12-induced. Moreover, R54 inhibited CXCL12 dependent pERK1/2 and pAKT and reversed the CXCL12 induced EMT in ovarian cancer cells. Targeting CXCR4 with the new antagonist R54 consistently reverted the mesenchymal transition in human ovarian cancer cells reducing migratory and chemoresistance features.